A common terminology for the external anatomy of centipedes (Chilopoda) - Bonato, Lucio (2010)
A common terminology for the external morphological characters of centipedes (Chilopoda) is proposed. Terms are selected from the alternatives used in the English literature, preferring those most frequently used or those that have been introduced explicitly. A total of 330 terms are defi ned and illustrated, and another ca. 500 alternatives are listed.